The influence of firm size on IPO oversubscription: evidence from Bursa Malaysia - Tajuddin, Ahmad Hakimi; Abdullah, Nur Adiana Hiau; Taufil Mohd, Kamarun Nisham (2017)
The purpose of this paper is to examine the influence of firm size on oversubscription of initial public offerings (IPOs) listed on the Bursa Malaysia from the period of 2005 to 2015. The presence of firm size in influencing oversubscription further enables us to test the information asymmetry argued by Beatty and Ritter (1986). Data of 254 IPOs over a period of 11 years were obtained from the websites of Bursa Malaysia. Multivariate regression analysis was carried out to test for the relationship between oversubscription and independent variables. The finding of the study shows that firm size has a significant and negative influence on oversubscription. The result indicates that large firm which have a proven track records would have lower information asymmetry and do not need to under price their IPOs to attract investors and decrease the probability of oversubscription.